High Emergency Lung Transplantation: dramatic decrease of waiting list death rate without relevant higher post‐transplant mortality. (27th May 2015) - Roux, Antoine; Beaumont‐Azuar, Laurence; Hamid, Abdul Monem; De Miranda, Sandra; Grenet, Dominique; Briend, Guillaume; Bonnette, Pierre; Puyo, Philippe; Parquin, François; Devaquet, Jerome; Trebbia, Gregoire; Cuquemelle, Elise; et al.
Summary Many candidates for lung transplantation (LT) die on the waiting list, raising the question of graft availability and strategy for organ allocation. We report the experience of the new organ allocation program, "High Emergency Lung Transplantation" (HELT), since its implementation in our center in 2007. Retrospective analysis of 201 lung transplant patients, of whom 37 received HELT from 1st July 2007 to 31th May 2012. HELT candidates had a higher impairment grade on respiratory status and higher Lung Allocation Score (LAS). HELT patients had increased incidence of perioperative complications (e.g., perioperative bleeding) and extracorporeal circulatory assistance (75% vs. 36.6%, P = 0.0005). No significant difference was observed between HELT and non‐HELT patients in mechanical ventilation duration (15.5 days vs. 11 days, P = 0.27), intensive care unit length of stay (15 days vs. 10 days, P = 0.22) or survival rate at 12 (81% vs. 80%), and 24 months post‐LT (72.9% vs. 75.0%). Lastly, mortality on the waiting list was spectacularly reduced from 19% to 2% when compared to the non‐HELT 2004–2007 group. Despite a more severe clinical status of patients on the waiting list, HELT provided similar results to conventional LT. These results were associated with a dramatic reduction in the mortality rate of patients on the waiting list.